3D Point Cloud Model of Süleymaniye Mosque Obtained by Terrestrial Laser Scanning - R. A. Kuçak; M. O. Mete; A. Dervişoğlu; R. M. Alkan; M. Yanalak (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Cultural heritage is the totality of all kinds of works and values belonging to a society, inherited from the past and desired to be transferred to the future for various reasons. Suleymaniye Mosque is important as a UNESCO World Heritage site because of its architectural magnificence and because it represents the Ottoman cultural heritage. Suleymaniye Mosque, an exemplary work of Ottoman architecture, was designed by Mimar Sinan and built between 1550-1557. So, 3D documentation of cultural heritage sites is essential, and the most commonly used methods for 3D documentation are LiDAR and photogrammetry. This study documented Suleymaniye Mosque in Istanbul using the laser scanning method. Laser point cloud data fusion was performed to combine the point clouds, and an accurate and detailed representation of the monument was obtained. In the study area, TLS measurements were performed with Leica P40 TLS to obtain an accurate and detailed representation of the Suleymaniye Mosque. A data fusion process was also performed with the Cyclone Register 360 Program to obtain a complete model of the study area. Terrestrial laser scanning (TLS) was effectively used to document the Suleymaniye Mosque using a Leica P40 laser scanner.